Effect of protriptyline on [Ca2+]i and viability in MG63 human osteosarcoma cells. (12th October 2016) - Su, Ching-Kai; Chou, Chiang-Ting; Lin, Ko-Long; Liang, Wei-Zhe; Cheng, Jin-Shiung; Chang, Hong-Tai; Chen, I-Shu; Lu, Ti; Kuo, Chun-Chi; Yu, Chia-Cheng; Shieh, Pochuen; Kuo, Daih-Huang; et al.
Abstract: Tricyclic antidepressants (TCA) have been clinically prescribed in the auxiliary treatment of cancer patients. Although protriptyline, a type of TCA, was used primarily in the clinical treatment of mood disorders in cancer patients, the effect of protriptyline on physiology in human osteosarcoma is unknown. This study examined the effect of protriptyline on cytosolic free Ca 2+ concentrations ([Ca 2+ ] i ) and viability in MG63 human osteosarcoma cells. Protriptyline between 50 and 250 μM evoked [Ca 2+ ] i rises concentration-dependently. Protriptyline induced influx of Mn 2+, indirectly implicating Ca 2+ influx. Protriptyline-evoked Ca 2+ entry was inhibited by nifedipine by 20% but was not altered by econazole, SKF96365, GF109203X, and phorbol-12-myristate-13-acetate (PMA). In Ca 2+ -free medium, treatment with protriptyline inhibited the endoplasmic reticulum Ca 2+ pump inhibitor thapsigargin-evoked [Ca 2+ ] i rises. Conversely, treatment with thapsigargin inhibited 45% of protriptyline-evoked [Ca 2+ ] i rises. Inhibition of phospholipase C (PLC) with U73122 failed to alter protriptyline-evoked [Ca 2+ ] i rises. Protriptyline at 50–250 μM decreased cell viability, which was not reversed by pretreatment with the Ca 2+ chelator 1, 2-bis(2-aminophenoxy)ethane-N, N, N', N'-tetraacetic acid-acetoxymethyl ester (BAPTA/AM). Collectively, our data suggest that in MG63 cells, protriptyline induced [Ca 2+ ] i rises by evoking Ca 2+ release from the endoplasmic reticulum and other stores in a PLC-independent manner, and Ca 2+ entry via a nifedipine-sensitive Ca 2+ pathway. Protriptyline also caused Ca 2+ -independent cell death.